Electrocatalytic reduction of CO2 to ethylene and ethanol through hydrogen-assisted C–C coupling over fluorine-modified copper - Ma, Wenchao; Xie, Shunji; Liu, Tongtong; Fan, Qiyuan; Ye, Jinyu; Sun, Fanfei; Jiang, Zheng; Zhang, Qinghong; Cheng, Jun; Wang, Ye (Nature catalysis, 2020)
Electrocatalytic reduction of CO2 into multicarbon (C2+) products is a highly attractive route for CO2 utilization; however, the yield of C2+ products remains low because of the limited C2+ selectivity at high CO2 conversion rates. Here we report a fluorine-modified copper catalyst that exhibits an ultrahigh current density of 1.6 A cm−2 with a C2+ (mainly ethylene and ethanol) Faradaic efficiency of 80% for electrocatalytic CO2 reduction in a flow cell. The C2–4 selectivity reaches 85.8% at a single-pass yield of 16.5%. We show a hydrogen-assisted C–C coupling mechanism between adsorbed CHO intermediates for C2+ formation. Fluorine enhances water activation, CO adsorption and hydrogenation of adsorbed CO to CHO intermediate that can readily undergo coupling. Our findings offer an opportunity to design highly active and selective CO2 electroreduction catalysts with potential for practical application.Electrocatalytic reduction of CO2 into multicarbon (C2+) products is a highly attractive route for CO2 utilization. Now, a fluorine-modified copper catalyst is shown to achieve current densities of 1.6 A cm−2 with a C2+ Faradaic efficiency of 80% for electrocatalytic CO2 reduction in a flow cell.